Membrane Lipid Peroxidation of HbAA Erythrocyte of Non-Malarious Participants Administered with Quinine - Chikezie, Paul Chidoka; Uwakwe, Augustine Amadikwa (Free Radicals and Antioxidants)
The erythrocyte membrane is susceptible to lipid peroxidation due to its high content of polyunsaturated lipids. The present study ascertained levels of lipid peroxidation of non-parasitized erythrocytes of non-malarious male participants administered with quinine. Determination of erythrocyte lipid peroxidation was by a monitor of levels of thiobarbituric acid reactive substances, measured spectrophotometrically by taking the sample absorbance at 432 nm against a reagent blank at 24 °C. Fifteen (15) non-malarious male (59-79 kg) participants of confirmed HbAA genotype between the age brackets of 21-34 yr enrolled for this study. Three (3) participants per group were administered with quinine according to the corresponding doses: 1.5, 3.0, 4.5 and 6.0 mg/kg (control; n = 3). At regular time interval of 3 h for 12 h, blood samples were withdrawn for determination of erythrocyte membrane lipid peroxidation. Erythrocyte membrane of participants administered with quinine exhibited relatively high levels of lipid peroxidation in a dose dependent manner. Generally, within 0-6 h, the four adminstered doses of quinine caused a time dependent elevation of lipid peroxidation. Further increase in time (t > 6 h) showed decreasing levels of lipid peroxidation in participants administered with quinine. Generally, the levels of erythrocyte lipid peroxidation in the presence of quinine showed 2 phase profile. The first stage showed increasing levels of lipid peroxidation at t less than 6 h after drug administration, followed by the second phase which showed decreasing levels of lipid peroxidation. The results showed that administration of quinine to non-malarious individuals elicited flux in erythrocyte lipid peroxidation.
Keywords: Quinine; Lipid peroxidation; Erythrocyte; Antioxidant